The Benefits of Teaching English in Multilevel Classes ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article discusses teaching English to multilevel courses, including obstacles, benefits, and perspectives on how to conduct multilevel classes.A multi-level classroom is one in which some students know the Roman alphabet and others do not. Finally, the term multi-level can refer to a group of students who collaborate and have a diverse range of talents.